1993
DOI: 10.1128/jb.175.17.5375-5383.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the tktB gene encoding a second transketolase in Escherichia coli K-12

Abstract: We isolated a transposon TnlO insertion mutant of Escherichia coli K-12 which could not grow on MacConkey plates containing D-ribose. Characterization of the mutant revealed that the level of the transketolase activity was reduced to one-third of that of the wild type. The mutation was mapped at 63.5 min on the E. coli genetic map, in which the transketolase gene (tkt) had been mapped. A multicopy suppressor gene which complemented the tkt mutation was cloned on a 7.8-kb PstI fragment. The cloned gene was loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 42 publications
(21 reference statements)
2
54
0
Order By: Relevance
“…Genes coding for DHAS from the methanolutilising yeast Hansenula polymorpha [70] [132,155] and E. coli [68,152]; three di erent forms of TK have been cloned from the desiccation-tolerant plant Craterostigma plantagineum [4].…”
Section: Sources Of Tkmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes coding for DHAS from the methanolutilising yeast Hansenula polymorpha [70] [132,155] and E. coli [68,152]; three di erent forms of TK have been cloned from the desiccation-tolerant plant Craterostigma plantagineum [4].…”
Section: Sources Of Tkmentioning
confidence: 99%
“…This was the ®rst convincing evidence for genetic heterogeneity of any TK. Since then two genetic variants have been found in the bacterium E. coli [68,152] and three in the plant C. plantagineum [4]. While it is still unclear why E. coli and S. cerevisiae have two di erent TKs it could be shown that only one of the three TK forms in C. plantagineum is expressed constitutively.…”
Section: Variant Forms Of Tkmentioning
confidence: 99%
“…Since all of these substitutions occur in a single block, we wonder whether compounded sequencing errors may provide a simple explanation for the discrepancy. However, consideration must also be given to the fact that several organisms have more than one transketolase gene (e.g., E. coli (Sprenger 1993;Iida et al 1993), S. cerevisiae (Schaaf-Gerstenschläger and Zimmermann 1993; Sundström et al 1993), and C. plantagineum (Bernacchia et al 1995), and the possibility of two transketolase genes in humans has not been ruled out.…”
Section: Gly29mentioning
confidence: 99%
“…A second transketolase, distinct from but closely related to the first, has been cloned in both Escherichia coli (Iida et al 1993) and S. cerevisiae (Schaaff-Gerstenschläger and Zimmermann 1993), although any unique functions and metabolic implications of these enzymes remain unclear. In the dessication-tolerant plant Craterostigma plantagineum, three distinct forms of transketolase have been cloned (Bernacchia et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate the presence in E. coli of another protein (YJCU) which is functionally equivalent to epimerase. It is remarkable to note, that other proteins of the oxidative pentose phosphate cycle, transketolase and ribose-5-phosphate isomerase, are also present as two isoforms in E. coli [16,17]. Fig.…”
Section: Resultsmentioning
confidence: 99%